TOWARD RELIGIOUS MODERATION: Mohammed Arkoun’s and Hasan Hanafi’s Perspectives on Indonesian Wasatiyah Islam - Muhtar, Fathurrahman (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract : This research examines the views of Mohammed Arkoun and Hasan Hanafi on Wasatiyah Islam in Indonesia. Both Muslim scholars emphasize the importance of interfaith dialogue and the wise application of religion. This research uses a literature review to collect data from the works of Arkoun, Hanafi, and other relevant sources on Islam and Wasatiyah in Indonesia. The results showed that Arkoun and Hanafi had a significant influence on Wasatiyah Islam in Indonesia. Wasatiyah Islam encourages interfaith harmony and religious diversity through dialog and inclusiveness. The research findings imply that the ideas of Arkoun and Hanafi are important for Wasatiyah Islam in Indonesia and can help develop a moderate and inclusive outlook.Keywords : Indonesia, Islam, Wasatiyah,  interfaith harmony,  religious diversity